Predictors of Mortality Among a National Cohort of Veterans With Recurrent Clostridium difficile Infection. (19th July 2018) - Appaneal, Haley J; Caffrey, Aisling R; Beganovic, Maya; Avramovic, Sanja; LaPlante, Kerry L
Abstract: Background: Though recurrent Clostridium difficile infection (CDI) is common and poses a major clinical concern, data are lacking regarding mortality among patients who survive their initial CDI and have subsequent recurrences. Risk factors for mortality in patients with recurrent CDI are largely unknown. Methods: Veterans Affairs patients with a first CDI (stool sample with positive C. difficile toxin(s) and ≥2 days CDI treatment) were included (2010–2014). Subsequent recurrences were defined as additional CDI episodes ≥14 days after the stool test date and within 30 days of the end of treatment. A matched (1:4) case–control analysis was conducted using multivariable conditional logistic regression to identify predictors of all-cause mortality within 30 days of the first recurrence. Results: Crude 30-day all-cause mortality rates were 10.6% for the initial CDI episode, 8.3% for the first recurrence, 4.2% for the second recurrence, and 5.9% for the third recurrence. Among 110 cases and 440 controls, 6 predictors of mortality were identified: use of proton pump inhibitors (PPIs; odds ratio [OR], 3.86; 95% confidence interval [CI], 2.14–6.96), any antibiotic (OR, 3.33; 95% CI, 1.79–6.17), respiratory failure (OR, 8.26; 95% CI, 1.71–39.92), congitive dysfunction (OR, 2.41; 95% CI, 1.02–5.72), nutrition deficiency (OR, 2.91; 95% CI, 1.37–6.21), and age (OR, 1.04; 95% CI, 1.01–1.07). Conclusions: In our national cohort of Veterans, crude mortality decreased by 44% from the initial episode to the third recurrence. Treatment with antibiotics, use of PPIs, and underlying comorbidities were important predictors of mortality in recurrent CDI. Our study assists health care providers in identifying patients at high risk of death after CDI recurrence.